Biomechanical Effects of a Novel Anatomic Titanium Mesh Cage for Single-Level Anterior Cervical Corpectomy and Fusion: A Finite Element Analysis - Zhang, Ke-rui; Yang, Yi; Ma, Li-tai; Qiu, Yue; Wang, Bei-yu; Ding, Chen; Meng, Yang; Rong, Xin; Hong, Ying; Liu, Hao (Frontiers in Bioengineering and Biotechnology, 2022)
BACKGROUND: The traditional titanium mesh cage (TTMC) has become common as a classical instrument for Anterior Cervical Corpectomy and Fusion (ACCF), but a series of complications such as cage subsidence, adjacent segment degeneration (ASD) and implant-related complications by using the TTMC have often been reported in the previous literature. The aim of this study was to assess whether a novel anatomic titanium mesh cage (NTMC) could improve the biomechanical condition after surgery. METHODS: The NTMC model consisting of two spacers which located on both sides of the TTMC which match the anatomic structure between the endplates by measuring the patients' preoperative cervical computed tomography (CT) data. The ranges of motion (ROMs) of the surgical segments and the stress peaks in the C6 superior endplates, titanium mesh cage (TMC), screw-bone interface, anterior titanium plate and adjacent intervertebral disc were compared. RESULTS: Compared with the TTMC, NTMC reduced the surgical segmental ROMs by 89.4% postoperatively. The C6 superior endplate stress peaks were higher in the TTMC (4.473-23.890 MPa), followed by the NTMC (1.923-5.035 MPa). The stress peaks on the TMC were higher in the TTMC (47.896-349.525 MPa), and the stress peaks on the TMC were lower in the NTMC (17.907-92.799 MPa). TTMC induced higher stress peaks in the screw-bone interface (40.0-153.2 MPa), followed by the NTMC (14.8-67.8 MPa). About the stress peaks on the anterior titanium plate, the stress of TTMC is from 16.499 to 58.432 MPa, and the NTMC is from 12.456 to 34.607 MPa. Besides, TTMC induced higher stress peaks in the C3/4 and C6/7 intervertebral disc (0.201-6.691 MPa and 0.248-4.735 MPa, respectively), followed by the NTMC (0.227-3.690 MPa and 0.174-3.521 MPa, respectively). CONCLUSIONS: Firstly, the application of the NTMC can effectively decrease the risks of TMC subsidence after surgery. Secondly, in the NTMC, the stresses at the anterior screw-plate, bone-screw and TMC interface are much less than TTMC, which decreased the risks of instrument-related complications after surgery. Finally, increases in IDP at adjacent levels are associated with the internal stresses of adjacent discs which may lead to ASD, therefore, the NTMC can effectively decreased the risks of ASD.